Design and development of orange peeler : an ergonomics approach - Fara Farhana, Abdul Basek (2010)
This thesis deals with the design and development of an orange peeler with an ergonomics approach. The objectives of this thesis are to design an orange peeler with an ergonomics approach by using SolidWork and simulate by using ALGOR. The purpose for this study is to prevent the musculoskeletal disorder problems when peeling orange. The scope of this project is that the validation of the orange peeler through simulation software is considered precise. As for methodology, the design is based on data from literature review and manual calculation. The design will justify the ergonomics principle and the finite element analysis was performed. The finite element model of design was analyzed using Static Stress with Linear Material Models. Two designs of orange peelers were constructed. The result comes out that peeler A has higher Stress von Misses than peeler B. From the result, it is observed that the designs still lacks in many parts in order to approach the ergonomics criteria. As a conclusion, objectives for the simulation is achieved with comparing the two designs. Thus, the conclusion is based on the literature review, the designed is ergonomics.